Lactobacillus casei SYF-08 Protects Against Pb-Induced Injury in Young Mice by Regulating Bile Acid Metabolism and Increasing Pb Excretion - Chen, Zhenhui; Tang, Ziyu; Kong, Jingjing; Chen, Lixuan; Liu, Jiaxin; Li, Yunting; Huang, Wanwen; Li, Wendan; Wu, Junlin; Zhao, Wei; Meng, Xiaojing; Fan, Hongying (Frontiers in Nutrition, 2022)
Pb poisoning affects infant growth and development. However, dimercaptosuccinic acid (DMSA) as the current therapy for Pb poisoning exerts relatively significant toxic side effects in infants. Therefore, identifying a non-toxic treatment in this regard is particularly important. In this study, we aimed to investigate the therapeutic effect of an infant feces-derived probiotic strain, Lactobacillus casei SYF-08 (SYF-08), on Pb poisoning in young mice. The Pb levels in the organisms were detected via inductively coupled plasma mass spectrometry, while the therapeutic effect of SYF-08 on Pb-induced neural system damage was explored via the Morris water maze test, hematoxylin-eosin staining, and immunohistochemistry. Additionally, the molecular mechanisms underlying the protective effects of SYF-08 against Pb-induced intestinal damage were also explored via histological staining, 16S rRNA sequencing, untargeted metabolomics, qRT-PCR, and western blotting. In vivo experiments revealed that SYF-08 reduced blood and bone Pb levels and increased urinary Pb excretion. Additionally, SYF-08 alleviated Pb-induced pathological damage to the brain and ultimately improved the learning and cognitive abilities of the young mice. This treatment also restored intestinal microflora dysbiosis, regulated bile acid metabolism, and inhibited the FXR-NLRP3 signaling pathway. It also resulted in fewer adverse events than the DMSA treatment. In conclusion, our results provided valuable insights into the therapeutic role of SYF-08 in Pb poisoning and also suggested that its administration can significantly alleviate the Pb-induced damage.